Analisa Kandungan Zat Gizi Makro, Serat, Natrium, Dan Kolesterol Pada Kue Khas Kalimantan Selatan - Nany Suryani; An Nisa Eliandha; Oklivia Libri (Jurnal Kesehatan Indonesia, 2021)
South Kalimantan is one of the areas rich in culinary. Traditional foods are traditionally-made food, and the manufacturing process uses simple equipment. South Kalimantan people have a habit of eating typical South Kalimantan cakes that are generally sweet, salty, and ready-to-eat. Consuming these cakes continuously in excessive amounts will cause degeneratif diseases (e.g., hypertension, diabetes mellitus, heart disease, stroke, and obesity). This research aimed to analyze the content of macronutrients (carbohydrates, proteins, fats), fiber, sodium, and cholesterol in the typical cakes of South Kalimantan. This was an observational study with a descriptive approach. Macronutrients, fiber, sodium, and cholesterol contents were determined using Nutrisurvey software. The analysis results on 33 kinds of typical South Kalimantan cakes using 100 g of cake showed that Amparan Tatak has the highest carbohydrates (137,8 g) and fiber (7,1 g), and Ipau Basumap has the highest protein (21,7 g) and sodium (511 mg) contents. Bingka Kentang has the highest fat content (22,4 g, and Bingka Barandam has the highest cholesterol content (486,2 mg). Based on the energy contribution categories, snacks were good to consume if they contributed to 10-20% of the total needs. The snack portion on an average day for adults should have 243,75 kcal energy, 36,5 g carbohydrates, 9,1 g protein, fat 6,8 g, fiber 3 g, 200 mg sodium, and 30 mg cholesterol. Thus, it is necessary to pay attention to daily snack consumption to avoid degenerative diseases.